Minnie's valentine - Higginson, Sheila Sweeny, 1966-; Loter, Inc. (New York : Disney Press, 2007)
Miss M. helps Mickey Mouse make a hat as a Valentine's Day gift for Minnie Mouse.
"Disney Mickey Mouse Clubhouse."
"Includes over 25 stickers!"--Cover.
"Playhouse Disney, on Disney channel"--Cover.
2.1
K-3.
K-3
Keywords: Mice -- Juvenile fiction; Valentine's Day -- Juvenile fiction; Mice -- Fiction; Valentine's Day -- Fiction; Mice -- Fiction; Valentine's Day -- Fiction